A study of performance measures and quality management system in small and medium enterprises in India. Issue 4 (14th December 2020) - Bagodi, Virupaxi; Thimmappa Venkatesh, Sreenath; Sinha, Deepankar
Abstract : Purpose: The paper aims to identify causality amongst small and medium enterprises' (SMEs') performance indicators, propose an integrated index of business performance and quality practices and investigate the effect of quality management system (QMS) on business performance. Design/methodology/approach: This study proposes a two-stage approach. In the first stage, the authors gathered responses with a questionnaire on variables affecting business performance and identified dimensions using exploratory and confirmatory factor analyses. Path analysis was carried out to identify causality between the dimensions. In the next stage, the validation of stage 1 findings was carried out to substantiate the proposition that QMS affects performance. Questionnaire survey and in-depth interviews were conducted during the second stage. The analysis was done following the case study protocol – within- and cross-case analysis and validated with supportive and conflicting literature. Findings: The results show that the employee – dimension is crucial to process effectiveness, customer satisfaction and finances. Customer satisfaction results from employee satisfaction and processes. QMS impacts processes and employee performance, thus establishes the causality between business performance factors and QMS. QMS impacts finances in the short run but yields long-term benefits and is dependent on two factors – degree of knowledge of quality practices and its application in business. Originality/value: This study reveals the performance dimensions of SMEs, their causality and the impact of QMS on performance. It suggests a shift from traditional approaches, correcting defects using statistical quality control approaches, to a sustainable growth path – a long-term approach. This study puts forward two associated indices – the business performance and the knowledge of quality practices and its application index.